Mine Towns : Buildings for Workers in Michigan's Copper Country - Hoagland, Alison K., 1951- (Book collections on Project MUSE., 2010)
During the nineteenth century, the Keweenaw Peninsula of Northern Michigan was the site of America's first mineral land rush as companies hastened to profit from the region's vast copper deposits. In order to lure workers to such a remote location--and work long hours in dangerous conditions--companies offered not just competitive wages but also helped provide the very infrastructure of town life in the form of affordable housing, schools, health-care facilities, and churches. The first working-class history of domestic life in Copper Country company towns during the boom years of 1890 to 1918, A.